Investigating the interaction between neuropsychiatry features and daily activities on social function in patients with Parkinson's disease with mild cognitive impairment - Yi-Ru Chen; Chun-Hsiang Tan; Hui-Chen Su; Chung-Yao Chien; Pi-Shan Sung; Tien-Yu Lin; Tsung-Lin Lee; Rwei-Ling Yu (BJPsych Open, 2022)
Background Social functioning is crucial for daily living and is an essential indicator of dementia in patients with Parkinson's disease. The pattern of social functioning in patients with Parkinson's disease without dementia (i.e. those who are cognitively intact or have mild cognitive impairment (PD-MCI)) and its determinants are unclear.